Managing NGOs for growth and change a case study of Proshika in Bangladesh - Sattar, M G; Afreen, Neena; M G Samdani Fakir (BRAC Research and Evaluation Division (RED), 2019)
The non-governmental organisations (NGOs) in South Asian countries have attained phenomenal growth, more so in Bangladesh. There has been manifold increase in the number of NGOs, their staff and operational budget NGO programmes have also undergone rapid expansion. These organisations arc however, facing difficulties in administering their diverse programmes and managing a diverse range of staff. A study was conducted on Proshika, a large NGO in Bangladesh, to examine how it has attained growth and handled management challenges. The study themes included (a) organisation and performance, (b) strategy, (c) participation, (d) leadership and succession, (e) gender, and (f) learning. Proshika works with 1.4 million rural and urban poor and operates wide range of programmes which include social mobilization, education, credit, employment and income generation, health and sanitation, housing, social forestry, ecological agriculture, policy advocacy, etc. Over the last ten years (1989-1998) there has been fantastic growth of Proshika as an organisation. The number of its programme participants increased by 3 50%, staff size rose by 460o/o, and there has been 40-fold increase of its operational budget during this period. Generous donors' support, continuing efforts in capacity development, staff motivation and incentives, and participatory approach to development contributed largely to the scaling-up Proshika. The study reveals that Proshika has so far managed its growth well. The founder leader has been providing good leadership which helped Proshika to get over an initial split of the organisation and develop it from a small scale into a big multifaceted organisation. But rapid growth has put strains on the management structures and systems. According to one recent review, overloads are becoming excessive. Rapid growth has also made a dent on the senior management which is overstretched and often uses 'crisis management approach' to major issues rather than strategic management.